Os Saberes locais e o ensino de botânico: diálogos entre saberes - Batista, Leandro Nogueira (2020)
This master thesis aimed to comprehend the possible articulations between local knowledge related to local agriculturists’ farming activities and the teaching-learning process in Botanic, focusing on high school. For this purpose, activities with different social agents were developed: four farmers were chosen in order to unveil the local knowledge about the cultivation, along with thirty-nine senior year students and the titular teacher of a public school from Parintins-Am. Said activities underwent distinct stages: first, monitoring of the farmers’ labour practices allowed us to know about their life experiences related to their crop. After this knowledge description, an articulation proposition with Botanic teaching was carried out along with the senior year students through a didactic sequence. Parallel to this, we talked to the titular teacher in order to verify how the knowledge is articulated in the classroom. The theoretical justification was grounded mainly on the thoughts of Geertz (2014), Kuhn (1998), Boaventura Santos (1988), Lévi-Strauss (1978, 2008); Merleau-Ponty (2018), Foucault (1999) and Fleck (2010), to reflect on science as a hegemonic knowledge at the expense of other non westernized knowledge built from worldly experience and perception itself. The methodological path was of a qualitative base subsided by field research with phenomenological procedures (MERLEAU PONTY, 2018). Results demonstrated that the variety of the farmers’ knowledge related to the cultivation of different plant species is built upon worldly experiences and the perception that allowed them to perfect the plantation techniques, which revealed ways of being, living, acting and thinking which fulfill the intellect’s demand. It is valid to emphasize the necessity of preserving these knowledges at the expense of an “amnesia” favored by the implantation of industrialized forms of production. We noted that the students’ view on Botanic is based on scientific classification formally learned and that the local knowledge is due to empirical knowledge through the medicinal use of plants. However, we consider that the developed activities permitted the articulation of local knowledge about manioc cultivation through Botanic teachings. We reaffirm that the possibilities of articulation may be extended and associated to other Botanic fields as from different plant species in detriment of local knowledge valuation based in a self-made tradition that maintains the necessity not only of subsistence but also the ways of living of many populaces.